COMPLICATIONS OF PLASMAPHERESIS IN COVID-19 PATIENTS AT PAF HOSPITAL MUSHAF - Afzal, Hania; Asif Naseer, Muhammad; Khalid, Muzammil (Infectious Diseases Journal of Pakistan, 2023)
Background: Plasmapheresis is a method of blood purification in which blood plasma and components are removed and treated from blood circulation. With advances in treatment of COVID-19, plasma exchange was found effective against disease complicated by cytokine storm syndrome. Plasmapheresis was started in our setup in January 2021. Study was conducted to observe adverse events related to procedure. Material and Methods: A hospital based descriptive case series was conducted from January 2021 to June 2021, in Pakistan Air Force Hospital Mushaf, Sargodha, Punjab, Pakistan. Adverse events like hypocalcemia, hypotension and cardiac arrest were observed in 44 plasmapheresis sessions. Data was collected by generating a proforma and was analyzed by using IBM SPSS. v.24. Results: Data from our study revealed that complications were seen in 25% of plasmapheresis sessions with most of the complications being minor and easy to manage and fatal events in 0.04% cases only. Complication during maintenance of Intra Venous line was seen in only one session, during procedure in 2 sessions and after procedure in 8 sessions. The only complication related to maintenance of Intra Venous access was atrial fibrillation in a single case [1]. Complications seen during procedure included hypotension in 1 session and cardiac arrest in one. Adverse events seen after plasmapheresis were apprehension & palpitation in one case, drowsiness in one, drowsiness and Surgical Emphysema at Intra Venous access site in one, Hypocalcemia in three, Hypocalcemia with drowsiness in one and Hypomagnesemia in one case. Conclusion: After interpretation of analysis and reviewing literature, it was seen that plasmapheresis is a safe procedure if it is used with caution and professional expertise. Key Words: Plasmapheresis, Cytokine Storm, Adverse Effects, Complications, COVID-19